Avaliação da influência do teor de cal nas propriedades reológicas e mecânicas das argamassas mistas de cimento para revestimento. - Amorim, Elanny Carolynne de Almeida (2023)
The rheological behavior of a mortar is represented by relations between the deformation of a fluid and the forces to which it is subjected, so that rheology is the science that studies the flow and deformation of matter by evaluating the relations between applied shear stress and its deformation over a given period of time. The mortars used for coatings comply with rheological concepts when analyzed in their fresh state, when they are manipulated and applied to their different uses, promoting good results in the hardened state. As it is a mixture of binders and inert materials, respectively Portland cement, hydrated lime and fine aggregates, it is natural that the proportions and quantities present of each of these components interfere with the behavior of the mortars, whether in their fresh (rheological) or hardened. The objective of this work is to present how variation in the content and type of hydrated lime influences the rheological properties of coating mortars, and its consequences also on the mechanical properties after hardening, based on tests carried out in the laboratory simulating field conditions. As the main conclusions of this study, the proposed methods proved to be relevant characterizations, with small variations in results. It was also observed that the increase in lime content has a positive effect on the rheological parameter, increasing its flow capacity in a flowing situation, as well as a negative effect on the properties of the mortar in the hardened state.